Pemanfaatan Linked Data untuk Meningkatkan Kualitas Information Knowledge pada Resources Game Online - Mohammad Yani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
This paper proposes an online game design that has resources with interoperability. Interoperability means the resources can share, re-used, and interlinked with another Unified Resources Identifier (URI). The game design is constructed by utilizing Linked Data concept where the resources are developed in the form of ontology. The resources are developed by both creating manually using Protégé and re-using from another URI’s. To get the resources from another URI’s SPARQL can be used through Apache Jena Fuseki server. SPARQL is a query used for Resource Description Framework (RDF) or Web Ontology Language (OWL). The result shows that retrieval data/information process by using SPARQL works well. The resources from another URI’s can be used and integrated with local resources. It means the quality of information knowledge is increasing in interoperability, where the resources can be shared, re-used, and interlinked.